The Management, Current Treatment Modalities and Reconstruction Techniques for Lip Cancer - Gökçe Tanyeri; Görkem Eskiizmir (Turkish Archives of Otorhinolaryngology, 2014)

(untitled)
The lips are important anatomic structures which have vital and social functions such as eating, drinking, phonation, speaking, kissing and expressing emotions. Squamous cell carcinoma is the most common histopathological type of lip cancer. Sun exposure, smoking, and chronic irritation have an important role in the etiopathogenesis. Lip cancers constitute a serious health problem and their treatment requires a multidisciplinary approach. The operability status of patients, comorbid disease and patient expectations, tumor stage, location, size, depth and characteristics should be carefully evaluated while planning the treatment of these cancers. The purpose of this article is to present contemporary treatment modalities in cancers of the lip, tumor staging and treatment planning, analysis of lip defects related to surgery, major principles and techniques of lip reconstruction.